Corporate Social Responsibility Disclosure Among MESDAQ Listed Companies - Mohd. Amran, Jaafar (2008)
The aims of this study to investigate influence of size, profit, gearing and industry type, and dependence on government on Corporate Social Responsibility (CSR) disclosure in MESDAQ listed companies, where CSR is the low awareness and lack of recognition that participation in the implementation of CSR in business operations. The methodology used in this paper is a cross-sectional study, which focuses on the information contained in annual reports for the year 2006. The study uses score index as a method to measure the degree of CSR. The findings are based on regression analysis, the study demonstrated the effectiveness of government influence, as dependence on government contracts. Institutionalization the Government of desire and commitment to CSR is perhaps the most appropriate to describe Malaysian CSR practices.